Limb circumference measurements contributing to the diagnosis of snake venom-induced compartment syndrome - Xiaoyan Xian; Zhen Jiang; Yan Ren; Shiyuan Tang; Yajun Liu; Ting Bai; Fang Chen; Li Ding; Shuyun Xu (Heliyon, 2024)
Background: The present study aimed to investigate the relationship between swollen limb circumference and compartment pressure after a snakebite and to evaluate the diagnostic value of the circumference difference between the healthy and affected sides and the circumference growth rate for snake venom-induced compartment syndrome (CS). Method: The study was based on a prospective cohort study of snakebite patients at the emergency department of West China Hospital from May 2021 to October 2022. The snakebite patients were divided into the CS and non-compartment syndrome (NCS) groups. The diagnostic value of the circumference of the swollen limb for the CS after snakebite was evaluated using a receiver-operating characteristic curve analysis, and the cut-off value of the circumference of the swollen limb for CS after snakebite was calculated with sensitivity and specificity. Result: The present study enrolled 115 patients with severely swollen limbs after snakebite. The mean age was 59.1 ± 13.6 years, with 58 (50.4 %) female cases and 57 (49.6 %) male cases. There were 33 (28.7 %) cases where the upper limbs were injured and 82 (71.3 %) cases where the lower limbs were injured. These patients were divided into CS (n = 19) and NCS (n = 96) groups. The area under the curve (AUC) for the 15 cm circumference difference and circumferential growth rate of the upper edge of the patella was 0.683 (95 % CI 0.508 to 0.858, P = 0.037), and 0.685 (95 % CI 0.512 to 0.858, P = 0.035). The optimal cut-off values for the 15 cm circumference difference and circumferential growth rate of the upper edge of the patella to distinguish CS and NCS were 2.8 cm (sensitivity = 76.9 %, specificity = 66.7 %) and 7 % (sensitivity = 76.9 %, specificity = 66.7 %), respectively. Conclusion: Limb circumference measurement is a non-invasive, convenient, effective, and repeatable bedside test that can assist clinicians in the early detection of suspected snake venom-induced CS in patients exhibiting limb swelling after snake bites.